Pengaruh Etos Kerja Dan Semangat Kerja Terhadap Efektivitas Kerja Karyawan Pada Badan Pendapatan, Pengelola Keuangan Dan Aset Daerah (BPPKAD) Kota Kediri - Fajar Adi Saputro; Ahmad Jauhari; Nur Hidayati (Journal of Creative Student Research, 2023)
Human resource management is one of the important factors in an agency. In order to achieve its goals, it requires quality human resources who are competent and qualified and consistent in every job. This research aims to determine the influence of work ethic and work enthusiasm on the work effectiveness of employees at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) of Kediri city. The sample in this study was 70 respondents consisting of civil servants and honorary employees. The tool for testing this research is using SPSS 25. Using proportionate stratified random sampling technique. By using multiple linear regression analysis, t test and F test, the results of this research are that work ethic has a significant effect on work effectiveness with a sig value of 0.000 < 0.05, work enthusiasm has a significant effect on work effectiveness with a sig value of 0.043 < 0.05. Work ethic and work spirit have a joint and significant effect on work effectiveness with a sig value of 0.000 < 0.05.